Characterization of Hazelnut Milk Powders: A Comparison of Spray-Drying and Freeze-Drying - Ermis, Ertan; Guner, Kubra Ozkan; Yilmaz, Mustafa Tahsin (WALTER DE GRUYTER GMBH, 2018)
Production of hazelnut milk powder (HMP) was investigated using maltodextrin (MD) as supporting material. Spray-drying and freeze-drying techniques were used to obtain the powder material. MD was added at concentrations of 5%, 10% and 15% (w/w) prior to drying. The powder properties were evaluated by determining flowing properties (Hausner ratio and angle of repose), thermal behaviour using DSC, molecular properties using FTIR, solubility and zeta potential. Hausner Ratio for both spray dried (SDHMP) and freze-dried (FDHMP) samples varied from 1.30 to 1.64 corresponding to very poor flow. The FDHM powder samples exhibited slightly lower Hausner Ratio values than SDHM powders. FTIR spectras showed that both SDHM and FDHM exhibited similar absorbance characteristics with slight differences. Lower endothermic transition temperatures were recorded from FDHMP when compared to SDHMP. The solubility in water for both powder samples ranged from 20 to 65 % depending on the drying method and MD content. Based on the residual moisture content, water activity, solubility and flowability, spray drying process was found to produce better quality powders compared to freeze drying process.
Keywords: hazelnut; spray drying; freeze drying; powder characterization; CORYLUS-AVELLANA L.; HIGH-PRESSURE HOMOGENIZATION; TURKISH TOMBUL HAZELNUT; PHYSICAL-PROPERTIES; FTIR; ALMOND; MALTODEXTRIN; PARAMETERS; VARIETIES; SUCROSE; Food Science & Technology